Conclusions: Learning Lessons and Moving Forward - Kirsten Roberts Lyer; Ilyas Saliba; Janika Spannagel (University Autonomy Decline: Causes, Responses, and Implications for Academic Freedom, 2023)
This final chapter discusses how university autonomy can be upheld and protected in a global environment of increasing attacks. It argues that strengthened international standards for institutional autonomy and self-governance of higher education institutions (HEIs), including international oversight, are crucial to halt the erosion of university autonomy. It identifies how international accreditation and ranking agencies could increase the costs for attacks on university autonomy and academic freedom by factoring this aspect prominently into their assessments of HEIs. Lastly, it focuses on what universities can do to strengthen their institutional resilience in the face of growing government interference in their autonomy. It proposes that as best practice, universities should continuously assess and mitigate risks, and proactively plan how to respond when interference occurs.
Additional information: The publication of the open access book "University Autonomy Decline: Causes, Responses, and Implications for Academic Freedom" was funded by the Open Societies Foundation and the Open Access Publishing Fund of the Leibniz Association.
Keywords: 330